2006
DOI: 10.1111/j.1755-6686.2006.tb00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Renal Care Practice in Europe: Centre and Patient Characteristics

Abstract: The European Practice Database (EPD) contains data from 8 countries including 276 centres and 21,861 dialysis patients. Comparing patients and centre characteristics, remarkable similarities and pronounced differences in renal practice between different European countries and between centres within each country were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…) in contrast to dialysis practices in Europe and the United States of America where more dialysis technicians and fewer nursing staff are used (Elseviers et al . , Ramanarayanan & Snyder , Wolfe ). Bennett et al .…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…) in contrast to dialysis practices in Europe and the United States of America where more dialysis technicians and fewer nursing staff are used (Elseviers et al . , Ramanarayanan & Snyder , Wolfe ). Bennett et al .…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…Francia exige la presencia permanente durante la hemodiálisis (HD) de al menos una enfermera por cada cuatro pacientes y una auxiliar por cada ocho 21 . Por último, un estudio que compara la práctica de cuidado renal en Europa, donde participaron ocho países (276 centros, con 21.861 pacientes) mostró que la razón paciente/enfermera (incluyendo enfermeras y asistentes) variaba en promedio entre 2,3 (Noruega) y 4,2 (Bélgica) 22 . Hay diferentes herramientas de medición de carga de trabajo que han sido utilizadas en enfermería.…”
unclassified
“…Patient‐to‐staff ratio differs between countries and units and should depend on the dependency and stability of the patients. An EDTNA/ERCA Research Board study found that the mean ratio was 4 patients (3.5 to 4.2) per nurse (Elseviers et al 2006).While an ideal patient‐to‐staff ratio cannot be defined, staff management must be able to identify the point at which routine assessments such as surveillance of access during haemodialysis is impossible due to the number of patients and/or their clinical profiles. All patients should be assessed for level of risk of VND and, if appropriate, an alarm device intended for monitoring venous needle dislodgement used Although all haemodialysis patients with an AV fistula or AV graft are at risk of VND, for most patients the risk can be minimized by secure taping and routine monitoring. For patients with a significantly higher risk of VND, the use of continuous monitoring using an appropriate blood leak detector should be considered.Staff need to identify patients who need to be more closely monitored, whether via observation or an alarm device, at each treatment session.…”
Section: Practice Recommendationsmentioning
confidence: 99%
“…Patient‐to‐staff ratio differs between countries and units and should depend on the dependency and stability of the patients. An EDTNA/ERCA Research Board study found that the mean ratio was 4 patients (3.5 to 4.2) per nurse (Elseviers et al 2006).…”
Section: Practice Recommendationsmentioning
confidence: 99%